2016
DOI: 10.1007/s00114-016-1372-1
|View full text |Cite
|
Sign up to set email alerts
|

Sexual selection leads to a tenfold difference in reproductive success of alternative reproductive tactics in male Atlantic salmon

Abstract: The precocious maturation of some male Atlantic salmon (Salmo salar L.) has become a textbook example of alternative mating tactics, but the only estimates of reproductive success available so far are either the collective contribution of precocious males to reproduction in the wild or individual reproductive success in oversimplified experimental conditions. Using genetic parentage analysis on anadromous and precocious potential spawners and their offspring, we quantified components of individual reproductive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
39
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(39 citation statements)
references
References 71 publications
0
39
0
Order By: Relevance
“…We also took advantage of the availability of observations obtained previously for the S. salar River Nivelle population for the 2010 and 2011 reproductive seasons (Tentelier et al, ) to assess: the effect of YOY sampling spatial extent [whole river in the present study and upper section of the river in Tentelier et al . ()]; sampling intensity [shallow in this study and exhaustive around spawning sites in Tentelier et al .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…We also took advantage of the availability of observations obtained previously for the S. salar River Nivelle population for the 2010 and 2011 reproductive seasons (Tentelier et al, ) to assess: the effect of YOY sampling spatial extent [whole river in the present study and upper section of the river in Tentelier et al . ()]; sampling intensity [shallow in this study and exhaustive around spawning sites in Tentelier et al .…”
Section: Methodsmentioning
confidence: 99%
“…()]; sampling intensity [shallow in this study and exhaustive around spawning sites in Tentelier et al . ()]; time of year [9 months after spawning in autumn in the present study and 3 months after spawning in early spring in Tentelier et al, ()], on estimation of N b . Effects of sampling spatial extent and sampling intensity were assessed by direct comparison of N b estimates with Tentelier et al .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…While mature male parr reproductive contribution can exceed anadromous male reproductive contribution at the population level (e.g. 25 to 56%19 and up to 87%21 of male reproductions in the Nivelle population in south of France), mature male parr individual reproductive success is far lower than anadromous male individual reproductive success due to a reduced matting success of mature male parr19. Evidence from experimental studies including artificial crosses followed by rearing in laboratory conditions and from studies in natural populations has demonstrated a genetic component for early male maturation in S. salar 15222324252627.…”
mentioning
confidence: 99%
“…Instead of artificial breeding, this study involved samples of naturally breeding adults (both anadromous breeders and mature male parr) and their offspring. Sampling procedure and family reconstruction are described in Tentelier et al . (2016 a , b ).…”
Section: Methodsmentioning
confidence: 97%